9th WCEAM research papers. Proceedings of 2014 World Congress on Engineering Asset Management - Amadi-Echendu, Joe E.; Hoohlo, Changela; Mathew, Joseph (Mechanical engineer) (Lecture Notes in Mechanical Engineering, 2015)
Engineering asset management encompasses all types of engineered assets including built environment, infrastructure, plant, equipment, hardware systems and components. Following the release of ISO 5500x set of standards, the 9th WCEAM addresses the hugely important issue of what constitutes the body of knowledge in Engineering Asset Management. Topics discussed by Congress delegates are grouped into a number of tracks including strategies for investment and divestment of assets, operations and maintenance of assets, assessments of assets condition, risk and vulnerability, technologies and systems for management of asset, standards, education, training and certification. These proceedings include a sample of the wide range of topics presented during the 9th World Congress on Engineering Asset Management in Pretoria South Africa 28 - 31 October, 2014 and complements other emerging publications and standards that embrace the wide ranging issues concerning the management of engineered physical assets.